Launching RTI Comprehension Instruction with Shared Reading: 40 Model Lessons for Intermediate Readers - Boyles, Nancy N. (Maupin House Pub., 2009)
Keywords: Reading (Elementary); Study and teaching (Elementary); United States; Reading comprehension; United States; Response to intervention (Learning disabled children); dept.rdg; faculty_collection

Hands-on Literacy Coaching - Boyles, Nancy N. (Maupin House Pub., 2007)
Keywords: Language arts teachers; Study and teaching; Training of; Language arts; Literacy; dept.rdg; faculty_collection

Constructing Meaning Through Kid-Friendly Comprehension Strategy Instruction - Boyles, Nancy N. (Maupin House, 2004)
Nancy's comprehension and written response strategies give teachers the first-tier Response-to-Intervention (RTI) help they need to get students off to a great start! Good readers think about reading while they are reading. But how does a teacher teach students to apply comprehension strategies as they read? By applying the explicit teaching model to comprehension strategy instruction, Dr. Nancy Boyles offers teachers an easy, effective, and innovative approach to improve students' reading comprehension. Using her book – rich with models, teacher-talk, and real-life examples – teachers learn how to explicitly teach students to apply comprehension strategies competently while they read. And with Dr. Boyles' detailed lesson plans and templates, teachers can embed comprehension strategy instruction into guided, shared, and independent reading for both literacy and content-area instruction. Constructing Meaning shows teachers: A kid-friendly way to introduce and model a blended repertoire of comprehension strategies concurrently, so students practice strategies as readers actually use them: flexibly and as an integrated whole while reading. How to refine students' comprehension of fiction and informational text during shared, guided, and independent reading with focused lessons in specific strategy applications. How to monitor students' progress in reading comprehension and comprehension-strategy use through follow-up activities, rubrics with discrete assessment criteria, and questions that make kids think. Teachers can reproduce classroom-ready visual supports from the book or customize them from the included CD.
Keywords: Reading comprehension; Study and teaching (Elementary); dept.rdg; faculty_collection

Teaching Written Response to Text: Constructing Quality Answers to Open-Ended Comprehension Questions - Boyles, Nancy N. (Maupin House, 2002)
Keywords: Composition and exercises; English language; Examinations; Study and teaching (Elementary); English language; dept.rdg; faculty_collection

The role of readability in today's classrooms - Gunning, TG (Topics in Language Disorders, 2003)
“The Role of Readability in Today's Classrooms” emphasizes the importance of providing students with materials on the appropriate level of challenge. Major readability formulas and leveling systems that might be used to assess the difficulty level of materials are reviewed. Because formulas are restricted to objective factors and leveling systems rely too heavily on subjective judgment, this article recommends using both objective and subjective factors when estimating readability levels. This article also recommends using readability/leveling systems as a way of noting textual difficulties that might need instructional intervention.
27 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000184947900004
Keywords: Leveling; Readability; Readability formulas; Reading; Reading materials; dept.rdg

Reading rescue: An effective tutoring intervention model for language minority students who are struggling readers in first grade - Ehri, Linnea C.; Dreyer, Lois G.; Flugman, Bert; Gross, Alan (American Educational Research Journal, 2007)
The Reading Rescue tutoring intervention model was investigated with 64 low-socioeconomic status, language-minority first graders with reading difficulties. School staff provided tutoring in phonological awareness, systematic phonics, vocabulary, fluency, and reading comprehension. Tutored students made significantly greater gains reading words and comprehending text than controls, who received a small-group intervention (d = 0.70) or neither intervention (d = 0.74). The majority of tutored students reached average reading levels whereas the majority of controls did not. Paraprofessionals tutored students as effectively as reading specialists except in skills benefiting nonword decoding. Paraprofessionals required more sessions to achieve equivalent gains. Contrary to conventional wisdom, results suggest that students make greater gains when they read text at an independent level than at an instructional level.
70 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000246958000007
Keywords: Beginning reading instruction; Language-minority students; Paraprofessionals; Reading acquisition; Struggling readers; Tutoring; dept.rdg

Development of writing knowledge in grades 2–8: A comparison of typically developing writers and their struggling peers - Lin, Shin ju Cindy; Monroe, Brandon W.; Troia, Gary A. (Reading & Writing Quarterly, 2007)
This study examined student perspectives about writing by interviewing both typically developing and struggling writers in Grades 2 through 8. The findings revealed a progressive developmental pattern of writing knowledge in which novice writers place more emphasis on the physical product and local meaning, while more experienced writers focus on global aspects, such as meaning and communication with an audience. In comparison, struggling writers focus on product over process even at the secondary level. Educational implications are discussed and include careful attention to the developmental level of the students during writing instruction.
30 citations (Crossref) [2023-10-31] Citation Key Alias: pop00051 tex.type: [object Object]
Keywords: dept.rdg

Teaching writing strategies to middle school students with disabilities - Monroe, Brandon W.; Troia, Gary A. (Journal of Educational Research, 2006)
Following less than 8 hr of instruction in the use of strategies to facilitate planning, self-regulation, and revising while writing opinion essays, a group of 3 middle school students with learning disabilities (LD) made substantial gains in each of 5 quality traits on which their papers were scored. On average, posttest scores of students with LD were better by 1 point on a 6-point scale than were those scores obtained by a group of LD students who served as controls. Participants' scores approached the level of writing performance exhibited by a group of peers without disabilities. The authors also observed treatment effects for number of functional essay elements; students who received strategy instruction gained an average of 1.3 functional elements from pretest to posttest. However, generalization to narrative writing was not obtained.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-325-822-977-127 tex.unique-id: [object Object]
Keywords: Effects on writing quality; Middle school students with learning disabilities; Strategies for supporting the writing process; dept.rdg